Terminologies in limited social environment - ABDULRAHMAN ALSAADI, ABDULLAH (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research examines the terms that meet the community’s needs at different times and places. It also discusses the development of the Arabic language, which has been confirmed through the development of judgments and intellectual assiduousness. In this context, there is a significant semantic difference between the two types of mercy. Finally, this research concludes that the Arabic language is rich and abundant in terms’ meanings; the environment plays a role in changing the term and developing the language, the importance of legislation in expanding the meaning of the terms, and social customs’ effects on changing meanings.